Reframing The Period Of The Sahaba And Tabi`In In The Archipelago: Acceptance Of Tradition - Hasbi, Ridwan; Rehayati, Rina; Martius, Martius; Kuakul, Yuttana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The presence of the Sahaba and Tabi`in in the archipelago is proven by the discovery of grave sites and historical records that corroborate the Arab theory of the entry of Islam. The period of the Sahaba and Tabi`in was the period that received the best certification from the Prophet with the phrase